A survey of ectoparasite infestation in dogs in Tehran, Iran - Jamshidi,Shahram (2012)
This survey was conducted to identify and estimate the frequencies of ectoparasites of dogs in Tehran, Iran. A total of 143 dogs attended at the Small Animal Hospital of the Veterinary School, the University of Tehran, were examined for the presence of ectoparasites and dermatological lesions. Ectoparasite specimens and blood samples were sent to parasitology and hematology laboratories, respectively. Ticks were the most frequent ectoparasite (36.4%, 52/143), followed by fleas (29.4%, 42/143), mites (25.9%, 37/143), and lice (8.4%, 12/143). Mixed infestations with two or more ectoparasites were detected in eight dogs. Rhipicephalus bursa was the most frequent ectoparasite in spring and summer. Ectoparasitic infestations were recorded mainly in large breeds and juvenile animals. Eosinophilia was more observed in dogs infested with Sarcoptes scabiei. The most common clinical sign, skin pruritus, was associated with mite and lice infestations. These results indicate that the tick R. bursa was the most prominent species of ectoparasite found in the evaluated group, followed by Ctenocephalides canis and S. scabiei var canis.